The Role of Digital Transformation in Enhancing Tax Compliance : A Case Study in Developing Economies (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
Digital transformation has emerged as a key driver of efficiency and transparency in various sectors, including taxation. This study explores the role of digital transformation in improving tax compliance, focusing on developing economies. Through a case study approach, the research investigates how digital tools and platforms enhance tax administration, reduce compliance costs, and improve taxpayer engagement. The study identifies key challenges, including technological infrastructure gaps and digital literacy, while highlighting successful implementations that have boosted voluntary tax compliance. The findings underscore the potential of digital transformation as a catalyst for sustainable economic growth in developing economies by broadening the tax base and reducing tax evasion. Policy recommendations for optimizing digital transformation initiatives in tax systems are also provided.